Ageing at the Base & Apex: Population Dynamics in 21st Century Africa - Muhammad Abdullahi Maigari; Aminu Surajo; Osamudiamen Aimee Chris (Sociology Study Program, Faculty of Social Science and Law, Universitas Negeri Jakarta, 2026)
Discourse on elderly people has not received sufficient attention from African academics and the government. Gerontology is one of the less popular areas of specialisation within Sociology, the social sciences, and the humanities in Africa. The lack of medical and social services specifically for elderly persons in African countries highlights the institutional neglect of the elderly across most parts of the continent. An increasing ageing population is a new phenomenon in Africa, but the turn of the 21st century has added a new dimension to the continent. Africa’s population is mainly youthful due to its relatively low life expectancy compared to developed countries. However, the number of elderly persons on the continent has continued to rise. This paper analysed data sets from various organisations to explain why Africa’s population is ageing both at the base and the peak. The Theory of Risk Society by Ulrich Beck (1992) is adopted to explain the challenges resulting from globalisation and the subsequent increase in longevity as living conditions or standards improve in Africa. The study found that longevity in African countries is driven by globalisation, which spreads a modern lifestyle and improved healthcare services for those who can afford them, even abroad. Additionally, the paper suggests that ageing at the lower level occurs in Africa because of the cultural belief that encourages Africans to have many children, and men to marry even in their 60s and 70s. As people live longer, both the young and elderly populations continue to contribute to high birth rates. This has resulted in Africa having a high fertility rate, alongside a rising elderly population. Longevity in Africa has significant implications, such as the lack of geriatric services in most African countries, which means that as Africans live longer, the consequences will be serious, especially given the absence of social protection policies to support the ageing population.